(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article analyses how migration affects eating habits and the process of dietary acculturation. As mobility patterns become more complicated and practically every country is affected by migration in some way, this period offers both opportunities and challenges. Migration has the ability to enhance not just the economics but also the cultural, political, and social lives of both the countries of origin and the country of destination. Various studies pointed out that food and dietary patterns were affected by the migration process. Similarly, in some cases, migrants’ culinary traditions and eating habits go with them. This is an effort to examine how traditional dietary practises and eating habits have changed and persisted throughout the migration.